MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN BERBASIS PROYEK DI KELAS IV SD NEGERI 2 PALANGGA - Abriatin, Riki; Mursidin, Mursidin; Yusuf, Aisyah (Program Pascasarjana Universitas Halu Oleo, 2019)
Abstract: This author aims to describe and analyze the problems in this study, is 1). Improving student learning activities through a project-based learning model in class IV SD Negeri 2 PalanggaKonawe Selatan District; 2) improve teacher teaching effectiveness by using project-based learning models in class IV SD Negeri 2 Palangga Konawe Selatan District; 3) improve student learning outcomes by using a project based learning model class IV SD Negeri 2 Palangga Konawe Selatan District.. Project-based learning is a learning model that provides opportunities for students to make project work in accordance with their learning competencies. The method used in this study is a project-based learning model. The population in this study were fourth grade students and numbered 15 students. The results of data analysis showed that in grade IV the average learning outcomes in the pre testtest reached (64.72) and after being given project-based learning models increased in cycles 1 to (65.7) and KKM (70). Conclusions in this study are through the implementation of learning with a project-based learning approach in class IV of SD Negeri 2 Palangga, Konawe Selatan District, which can increase Student Learning Activities by 66.22% in cycle I and 88% in cycle II and teacher teaching effectiveness of 65.80% I and 85.37% in cycle II. In addition, the results of student learning tests in the first cycle of 10 students from 15 students (66.66%) achieved learning completeness and the second cycle increased the results to 12 students from 15 students (93%).Keywords: Activity; effectiveness; learning outcomes; project-based learning